Eksistensi Mafqud (Solusi Atas Masa Tangguh Bagi Istri Dan Status Ahli Waris) - Miftakur Rohman (MASADIR: Jurnal Hukum Islam, 2021)
Abstract: Natural phenomena such as natural disasters are part of sunnatullah, of course there are wisdoms and problems that arise from them. Floods, landslides, fires, and even drought are among the examples. From this incident some people died, were injured and people were missing. Missing people create problems for the household, especially for wives who need certainty to remarry, as well as the status of their heirs. This issue attracted the attention of scholars to provide legal clarity and was responded to with several answers. For the tough period a wife can marry, first, the missing person is confirmed to have died. Second, waiting four years and four months and ten days as iddah for a wife whose husband died. Third. According to the judge's decision. However, if the mafqud returns there are 2 opinions. First, a wife is still the second husband's wife. Second, a husband who is mafqud can withdraw his wife or give her compensation for a mitsil dowry. Meanwhile, the issue of the status of the heir of mafqud. First. The wealth may not be distributed until it is clear that the mafqud has passed away or the death of the majority of people his age. Second, if the inheritance has been divided and the mafqud arrives, the heir must return it or replace it. Key word: Mafqud, Tough Period, Status of Heirs